ASSESSING THE EFFECT OF CORPORATE GOVERNANCE, LEVERAGE, AND FINANCIAL DIFFICULTY - Shavila, Dania Adelia; Purwanto, Agus (Kesatuan Press, 2025)
This study investigates how corporate governance mechanisms affect financial distress, with leverage as a moderating factor, in transportation and logistics firms listed on the Indonesia Stock Exchange from 2018 to 2023. The mechanisms considered include managerial and institutional ownership, the board of commissioners, the board of directors, and the audit committee. Financial distress is assessed using the Altman Z-score, where higher values reflect better financial health. The results show that managerial ownership, institutional ownership, the board of commissioners, and the board of directors are associated with stronger financial conditions. At the same time, the audit committee does not have a notable effect. Leverage does not moderate managerial ownership's role but strengthens other governance mechanisms' influence on financial health. These outcomes underline that governance effectiveness in preventing distress depends on ownership structure, board quality, and leverage. The study adds value to the literature by presenting evidence from Indonesia's transportation and logistics firms and suggests practical steps such as enhancing governance independence and managing debt prudently.